Unleash liquidity constraints or competitiveness potential: The impact of R&D grant on external financing on innovation - Byunggeor Moon (European Research on Management and Business Economics (ERMBE), 2022)
This paper uses Korea's internal data on R&D programs to analyze how the receiving of R&D impacts the amount of subsequent external financing for technological innovation received by R&D firms. We address sample selection and endogeneity issues that arise when estimating the impact of R&D policy by utilizing a matching method using unique features of Korea's R&D grant programs. Our empirical results show that firms that receive R&D grants further receive 22%-32% less external financing compared to those who do not receive R&D grants, though there are some differences in the statistical significance of the results based on the specification of the regression model. This is consistent with the view that R&D grants reduce firms' liquidity constraints, or that government support effectively crowds out funding from the financial market.
Keywords: D22; H32; O32; 650; External financing; Innovation policy; Liquidity constraints; R&D grant